Radioisotope studies of the Tisza river basin, Uzhansky masif - Svatiuk N.І.; Roman V.І.; Pop О.М.; Simkanich О.І.; Pylypchynets І.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
The results of applying nuclear-physical research methods of determination of the radioisotope composition of bottom sediments and soils of the Tisza river basin, on the example of the Uzh river on the Transcarpathian territory are presented. The database of contents for natural and man-made gamma-active nuclides is obtained using the low-background gamma spectrometry method. The results obtained are essential for setting the standards for their content and for the study of mountain areas. The possibility to establish U/Th/K chemical components in the bottom sediments of the Uzh river is shown. The results of radioisotope research allow modeling the processes of migration pf gamma-active nuclides from reservoirs into the soil horizons of the studied areas. These data are important for predicting the transboundary migration of gamma-active nuclides.